1995
DOI: 10.1007/bf00329800
|View full text |Cite
|
Sign up to set email alerts
|

Associational resistance and shared doom: effects of epibiosis on herbivory

Abstract: The potential for spatial associations between palatable and unpalatable plant species to reduce herbivore pressure on the palatable species has been described as associational resistance, associational refuge or associational defense for numerous terrestrial and marine communities. One of the closest associations between species-epibiosis-has not been thoroughly investigated in this regard. In this study we evaluated how different associations between host seaweeds and epibiotic plants and animals influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
207
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 222 publications
(210 citation statements)
references
References 37 publications
1
207
1
1
Order By: Relevance
“…Details on methodology and an expanded presentation or data are available in Wahl & Hay (1995), but a short overview is provided below. Most prey algae were collected between 0.5 and 2 m below MLW from jetties and pilings around Morehead City and Beaufort (32 42 0 N, 76 41 0 W), North Carolina, USA.…”
Section: Herbivore-prey Interactionsmentioning
confidence: 99%
“…Details on methodology and an expanded presentation or data are available in Wahl & Hay (1995), but a short overview is provided below. Most prey algae were collected between 0.5 and 2 m below MLW from jetties and pilings around Morehead City and Beaufort (32 42 0 N, 76 41 0 W), North Carolina, USA.…”
Section: Herbivore-prey Interactionsmentioning
confidence: 99%
“…Wahl & Hay's (1995) study of epibiotic associations between host seaweed and some plant and animal epibionts showed that associations included both positive and negative e¡ects. The outcome,`associated resistance' or`shared doom', was highly in£uenced by the relative densities of the species involved.…”
Section: Introductionmentioning
confidence: 99%
“…L. littorea is one of the most common gastropods at North Atlantic shores (Bertness, 1999) with a diverse epibiont community (Wahl and Hay, 1995;Buschbaum and Reise, 1999). In our study area, epibionts of L. littorea are mainly barnacles with up to 70% of snails on lower intertidal mussel beds being strongly covered with barnacles (Buschbaum and Reise, 1999).…”
Section: Introductionmentioning
confidence: 81%